Fab Helmet: ventilación mecánica no invasiva para pacientes con COVID-19 (Repertorio Científico, 2022)
Manufacture of the Fab Helmet: Non-Invasive Mechanical Ventilation for Patients with COVID-19.  Objective: This article aims to report the lessons learned from the development of the Fab Helmet. Method: Interdisciplinary and interinstitutional work for the elaboration of the device, considering those imported from other countries and used in national hospitals, but also the necessary and possible adaptations for Costa Rica and its reality. This implies that both materials available in the national market and the type of components of the device had to be compatible to work adequately in the conditions of Costa Rican health system. Results: Construction of the prototype suitable for Costa Rica, replicable with national materials and staff; supplying the medical system with more than 200 Fab Helmets, documentation and complete systematization of the process; obtaining the emergency permission for using the device, the operating permission for manufacturing medical and dental devices in UNED's Fabrication Laboratory and the only sanitary registration for category 2 Biomedical Equipment and Material given to a public university. Conclusions: Work process carried out left a series of lessons learned for both UNED team and the doctors involved in the project
Keywords: design; digital fabrication; prototype; interface; Fab Lab; health